Portuguese consumer: attitude and behavior towards consumption of chestnuts - Ribeiro, Maria Isabel (2019)
Worldwide, there is ever more increase in health consciousness. Consumers are far more information-seeking and nuts carry an overall healthy image. In Portugal, in addition to its functional benefits, chestnut carries rich emotional associations. Chestnut is deeply rooted in the Portuguese economy, gastronomy, and cultural heritage, as exemplified by the Portuguese saying: “In Saint Martin’s day; we eat chestnuts and drink the wine”. This work intends to understand the behavior of Portuguese chestnut consumers, their preferences, uses, purchasing habits and perceptions on the benefits of chestnut consumption. A cross-sectional study was carried out based on a sample of 320 individuals. The consumers inquired buy, on average, 6.5 Kg/year. Most of them purchase fresh chestnuts and do so occasionally, mainly in commercial stores, fairs or directly to the producer. They prefer to buy the chestnut unpackaged and the most valued attributes are quality, size and price. Still, the awareness about the distinct benefits of chestnuts is somewhat sketchy, as a significant part of respondents have bad or insufficient knowledge about its nutritional properties. These findings signal the need to better communicate the nutritional qualities and potential beneficial health effects of chestnut consumption and bet in R&D of new food, therapeutic and cosmetic products from chestnut.